Прогнозування механічних властивостей металів з обробленою поверхнею - Злобін, Павло Павлович (Харківський національний автомобільно-дорожній університет, 2025)
Object of research: relationship between structure and mechanical properties of St6 steel. Purpose of work: assessment of the mechanical properties of the metal based on the influence of the microstructure parameters and the crystal structure of the steel. Research methods: X-ray analysis, optical microscopy, mechanical studies. In the qualification work, studies were conducted on samples of structural steel St6, to which various heat treatment regimes were applied, in order to assess the influence of the parameters of the microstructure and crystal structure of the steel on their mechanical properties. The obtained models were analyzed for the feasibility of their use for predicting the mechanical properties of St6 steel.
Prediction of mechanical properties of surface-treated metals
Keywords: X-ray radiation; phase analysis; crystal lattice; diffract pattern; microstructure